Julia The Apostate - Bacon, Josephine Daskam, 1876-1961 (Salt Lake City, UT : Project Gutenberg, 2007)
"Julia The Apostate" by Josephine Daskam Bacon is a novel written in the early 20th century. This work explores themes of tradition versus modernity through the character of Miss Julia Trueman, who grapples with changing societal norms amidst her more progressive nieces, Carolyn and Elise. The narrative captures the dynamic of family relationships while delving into the tensions between old-fashioned values and contemporary lifestyles. The story revolves around Aunt Julia, a woman rooted in her traditional ways, who becomes increasingly perplexed by her modern surroundings and the behaviors of her nieces. As they attempt to introduce her to their contemporary social circle and ideologies, including new literary and artistic movements, Julia often finds herself at odds with their values. The tension culminates when she unexpectedly reconnects with a long-lost cousin, Lorando Bean. The pair strike up a romantic relationship, contrasting Julia's earlier struggles with her identity and modern society. Ultimately, Julia's journey reflects an internal transformation, as she accepts both her love for the country and her desire for companionship, embracing a new chapter of life with Lorando. (This is an automatically generated summary.)
Release date is 2007-11-06
Produced by David Widger
Keywords: Middle-aged persons -- Fiction; Love stories, American